knee osteoarthritis: An Updated Review for Physical Therapists, Nursing, and Pharmacists - Alharbi, Hussa Fraih Moodhi; Rabab Mohammed Ali Alsaleh; Yasir Mohammed Mousa Alajam; ‏Salman Hassan Mohammed Alhathiq; Rashed Sultan Ali Alonazi; Faisal Abdullah Al Faisal; Nasser Abdullah D Alkhurayyif; Abdulaziz Ibrahim M Alfaisal; Fahd Mohammed Alharbi; Abdulrahman Mohammed Hakami; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Knee Osteoarthritis (KOA) is a prevalent, degenerative joint disease and a leading cause of pain and disability globally. Its management is a significant challenge for healthcare systems, necessitating effective, conservative strategies to alleviate symptoms and improve function. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to provide an updated, comprehensive analysis of the efficacy, mechanisms, and comparative value of various physical therapy modalities for KOA, tailored for physical therapists, nurses, and pharmacists involved in patient care. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The article employs a systematic literature review methodology, evaluating a range of physical therapy interventions. These include traditional techniques like acupuncture and moxibustion, and modern modalities such as therapeutic ultrasound, shortwave diathermy, Pulsed Electromagnetic Field (PEMF) therapy, low-intensity laser therapy, and electrotherapy across low-, mid-, and high-frequency ranges. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The analysis confirms that all reviewed modalities can effectively reduce pain and improve function in KOA patients. Each therapy operates through distinct mechanisms—neuromodulation, thermal effects, photobiomodulation, or electromagnetic stimulation. The review highlights that combining modalities with complementary mechanisms often yields superior, synergistic outcomes compared to monotherapy. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> There is no single superior physical therapy for all KOA patients. A pragmatic, multimodal approach is recommended, integrating foundational exercise and education with accessible, low-cost options (e.g., moxibustion, electrotherapy) and escalating to technology-intensive modalities (e.g., PEMF, laser) based on individual patient needs, clinical phenotype, and resource availability.